(untitled) (Research, Society and Development, 2020)
The present study aimed to establish a reflection on the importance of ludomotor programs in the treatment of autistic children. As an methodological strategy, an integrative literature review was used, which consisted of a survey of articles, dissertations and theses published in the databases: SciELO, LILACS, BVSPSI, PePSIC and the CAPES Journal Portal, to verify which motor programs have already been carried out. with autistic children. The survey results showed the existence of 15 studies that used in their methodology a motor program for autistic children whose intention was to benefit motor development, as well as some articles that analyzed aspects of aggressive, stereotyped, social, quality of life and academic performance . It was concluded through the analyzed articles that when autistic children are monitored and participate in organized and systematic physical activity programs, they are able to enhance their motor, cognitive and affective proficiency.